2023
DOI: 10.1002/pssa.202200683
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mechanical Strain in AlGaN/GaN HFETs

Abstract: Herein, the influence of mechanical strain induced by passivation layers on the electrical performance of AlGaN/GaN heterostructure field‐effect transistor is investigated. We studied the physical mechanism of a threshold voltage (Vth) shift for the monolithically fabricated on/off devices reported earlier by our group. For that, theoretical calculations, simulation‐based analysis, and nano‐beam electron diffraction (NBED) measurements based on STEM are used. Strain distribution in the gate vicinity of transis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…However, previous work conducted on FBH devices have already established the influence of induced mechanical stress through passivation layers and/or gate metallization on GaN HFETs' characteristics, such as gate leakage and threshold voltage [9,10]. Earlier studies have demonstrated that mechanical stress induced during the fabrication process was transferred to the epitaxial layers beneath the gate region [11]. In the case of W1, the strained gate metal transfers compressive mechanical stress into the piezoelectric AlGaN/GaN epitaxial stack.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous work conducted on FBH devices have already established the influence of induced mechanical stress through passivation layers and/or gate metallization on GaN HFETs' characteristics, such as gate leakage and threshold voltage [9,10]. Earlier studies have demonstrated that mechanical stress induced during the fabrication process was transferred to the epitaxial layers beneath the gate region [11]. In the case of W1, the strained gate metal transfers compressive mechanical stress into the piezoelectric AlGaN/GaN epitaxial stack.…”
Section: Resultsmentioning
confidence: 99%